KOMPETENSI PUSTAKAWAN DALAM MEMENUHI KEBUTUHAN INFORMASI STANDAR DI KAWASAN PUSPIPTEK SERPONG - Rahartri Rahartri (Perpustakaan Nasional RI, 2019)
The Research Center for Science and Technology (Puspiptek) is an integrated area to please a number of reseacrh center on Indonesian Institute of sciense (LIPI), Agency for the Assesment and Application of technology (BPPT) an National Nulear Energy Agency (BATAN). Puspiptek han an area of 460 ha with 50 R D center and employs more than 5,000 people. Standart information is nuch needed by the R D center in Puspiptek area. Users’ demand for the latest standard information is insreasing, while the standard information resources possessed by libraries are limited. Therefore, libraries, as the spearhead of information services, need to obtain standard information resources form various information resources throughout the world. This paper discussed the standard information resources which are greatly needed and can be easily accessed by Puspipytek users.